variabel Investasi Asing Langsung dan Pertumbuhan Ekonomi di Indonesia dari tahun 1981-2021: Pendekatan Granger Causality Test - C. Bolang, Rikhard T. (LPPM University 17 Agustus 1945 Samarinda, 2022)
This research aims to identify and analyze the direction of the causal relationship between Foreign Direct Investment (FDI) and Economic Growth (GDP) in Indonesia in 1981-2021. The data used is secondary data. Secondary data is sourced from the World Bank website via the Indodapoer website. The analytical tool used to determine the direction of causality is using the Granger Causality Test. In addition to looking at the two-way relationship between Foreign Direct Investment and Economic Growth, this research also examines the analysis of the effect of Foreign Direct Investment on Indonesia's Economic Growth in the short and long term which is tested using the Error Correction Model (ECM).Based on the results of the ECM analysis, it was concluded that there is a long-term and short-term relationship between FDI and GDP in Indonesia. However, after conducting a causality analysis using the Granger Causality Test up to the fifth lag, it is concluded that there is no two-way relationship between Indonesia's FDI and GDP, but only a one-way relationship, namely Indonesia GDP to FDI.